1986
DOI: 10.1073/pnas.83.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Small heat shock proteins of Drosophila associate with the cytoskeleton.

Abstract: Fractionation of heat-shocked Drosophila melanogaster Kc cells reveals that both the small heat shock proteins (hsp28, -26, -23, and -22) and vnmentin-like intermediate filament proteins (EFPs) are abundantly represented in the nuclear fraction. Cofractionation of the IFPs with nuclei is due to the collapse of the IFP network against the nucleus upon heat shock, raising the possibility that cofractionation of the small hsps is by a similar mehanis. Indirect Immunofluorescence supports this possibility. In sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
2

Year Published

1988
1988
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 29 publications
1
50
0
2
Order By: Relevance
“…It has been suggested that the distribution of the low-MW HSPs in the detergent-insoluble nuclear-cytoskeletal fraction after heat shock is a consequence of such filament collapse (30). Although we cannot rule out this possibility entirely, we have shown here that treatment of cells with various other agents that promote the collapse of the intermediate filaments does not result in the redistribution of the 28-kDa protein into the insoluble fraction.…”
Section: Discussionmentioning
confidence: 50%
“…It has been suggested that the distribution of the low-MW HSPs in the detergent-insoluble nuclear-cytoskeletal fraction after heat shock is a consequence of such filament collapse (30). Although we cannot rule out this possibility entirely, we have shown here that treatment of cells with various other agents that promote the collapse of the intermediate filaments does not result in the redistribution of the 28-kDa protein into the insoluble fraction.…”
Section: Discussionmentioning
confidence: 50%
“…In contrast to earlier reports on the nuclear localization of small HSPs in heat-shocked cells of D. melanogaster (5,35,58,62) and plants (36) which were based on cell fractionation procedures, it is now firmly established that the mass of small HSPs in D. melanogaster (2,19,34), vertebrates (8,17), and plants (47) is in fact contained in cytoplasmic aggregates concentrated in the perinuclear region. A clue to the reinvestigation of previous data was the detection and biochemical characterization of these aggregates (heat shock granules [HSGs]) in tomato cell cultures (42,43,46,47).…”
mentioning
confidence: 43%
“…1) reveal three classes: (i) the bulk of mRNAs, which are nontranslated during heat shock but are preserved (Fig. 1H); (ii) a few control mRNAs whose translation continues during heat shock, e.g., mRNAs cod- (18,57 (14,17,22,34,(64)(65)(66) (17,34). The close location is impressively illusosition of prosomes (1) and pre-HSGs (2) trated by a freeze fracture image of chicken cells showing .…”
Section: Discussionmentioning
confidence: 99%
“…Nover et al (20) postulated that hs granules are unique to plants as no structure analogous to hs granules has been detected in animal systems. Unlike the cell-wide distribution of the low mol wt hs proteins in plants (19), the low mol wt hs proteins of Drosophila are associated with elements of the cytoskeleton during hs (13). During recovery, they are found in 20S RNP particles similar to prosomes, a class of scRNP particles implicated in the negative control of mRNA translation (3).…”
Section: Discussionmentioning
confidence: 99%
“…6). Sedimenting in advance of the polysome peak was a broad shoulder of absorptive material presumably representing the hs granules (fractions [6][7][8][9][10][11][12][13][14]. This material contained the majority of the radioactivity.…”
Section: Distribution Of Heat Shock Proteins In Ribosome Preparationsmentioning
confidence: 99%